Mechanism of SiOx particles formation during CVD graphene growth on Cu substrates. (November 2018) - Ge, Xiaoming; Zhang, Yanhui; Chen, Lingxiu; Zheng, Yonghui; Chen, Zhiying; Liang, Yijian; Hu, Shike; Li, Jing; Sui, Yanping; Yu, Guanghui; Jin, Zhi; Liu, Xinyu
Abstract: For graphene grown on Cu substrate via chemical vapor deposition (CVD), numerous nanometer particles are distributed along the graphene grain boundaries or evenly on the circumjacent substrate surface. The particles form new nucleation centers of graphene or destroy the graphene membrane during growth. In order to clarify the origin of particles, the formation process was studied by etching graphene at high temperature with different atmospheric pressures. We demonstrated that the formation of the particles is closely related to the competition of hydrogen and oxygen during growth; we also confirmed that the main component of particles was SiOx by energy dispersive spectrometry (EDS) measurement in transmission electron microscopy (TEM). Finally, on the basis of the formation mechanism, we proposed efficient approaches to reduce SiO x particles that improve the quality of graphene during actual CVD preparation process. Graphical abstract: Image 1 Highlights: The formation mechanism of SiO x particles is closely related to the competition of hydrogen and oxygen impurity during graphene growth. Hydrogen etches quartz to produce silicon, and then oxygen impurity react with silicon to produce SiO x particles in the case of hydrogen significantly reduced in the system. The simplest and efficient measure to reduce SiO x particles is to avoid the sharp drop of hydrogen concentration during CVD.